Separating effects of orthographic similarity and contour summation in the identification of masked letter strings. - Humphreys, G; Olson, A (2001)
We separated effects of contour summation and orthographic similarity under masking conditions, by comparing identification with simultaneous and sequentially presented letter strings, which either did or did not overlap spatially. With overlapping simultaneous stimuli, performance was better for strings with similar contours than for strings with the same letters (the orthographic similarity condition). This suggests that contour summation effects were strongest in the condition where stimuli had similar contours. With sequential presentations, performance in the similar contour and the orthographically similar conditions was equated when the stimuli were overlapping. However, effects of contour summation decreased when prime and target letters were spatially displaced, whereas performance in the orthographically similar condition was maintained. We conclude that effects of orthographic similarity can be distinguished from effects of contour summation, under masking conditions.